What is the standard form of y=(2x – 3)(x+4) ? Algebra Polynomials and Factoring Polynomials in Standard Form 1 Answer Vivek A. Jan 25, 2017 y = 2x^2 + 5x - 12 Explanation: y = (2x - 3)(x + 4) We can write it as follows: (2x - 3)(x + 4) = y 2x(x + 4) - 3(x + 4) = y (2x)(x) + (2x)(4) - (3)(x) - (3)(4) = y 2x^2 + 8x - 3x - 12 = y 2x^2 + 5x - 12 = y.Now, the equation is in its standard form. Answer link Related questions What is a Polynomial? How do you rewrite a polynomial in standard form? How do you determine the degree of a polynomial? What is a coefficient of a term? Is x^2+3x^{\frac{1}{2}} a polynomial? How do you express -16+5f^8-7f^3 in standard form? What is the degree of 16x^2y^3-3xy^5-2x^3y^2+2xy-7x^2y^3+2x^3y^2? What is the degree of the polynomial x^4-3x^3y^2+8x-12? What is the difference between a monomial, binomial and polynomial? How do you write y = 2/3x + 5 in standard form? See all questions in Polynomials in Standard Form Impact of this question 7303 views around the world You can reuse this answer Creative Commons License